The Islamization of The Malay Worldview A Study of Malay Historical Literature Taj al-Salatin - Nabila Yasmin (IAIN Bengkulu, 2020)
The Islamization of the Malay Worldview: A Study of Malay Historical Literature Taj al-Salatin This paper attempts to examine Taj al-Salatin as one of proofs of the islamization of Malay worldview in classical literature. The method used in this article is historical method and content analysis. The study shows that Islam has major influence upon the Malay worldview even it appears in a work on genre of Mirror for Princess like Taj al-Salatin. Taj al-Salatin is a work written by Bukhārī al-Jawhārī and designed with the aim of advising future kings and their executive officers (e.g., viziers, judges) on statecraft, how to rule best their subjects and to lead a decent life in accordance with the stipulations of Islamic ethics (akhlāq). The book is arranged in twenty-four chapters, dealing with the role of viziers, royal justice, and the sacred authority of kings. The first four chapters is discussed the key elements in Islam; the nature of man, the nature of God, the nature of the world and the nature of afterlife. In conclusion, notwithstanding that the book on genre of Mirror for Princess, Taj al-Salatin elaborated the discussion of knowing God, the nature of man and the nature hereafter in first four chapters. Such elaboration proved that Islamization of worldview did take place and it also appeared in many other writings of the scholars in this part of archipelago.